Development of an HIV Clinical and Research Database for South Africa - Kanter, A. S.; Spencer, D. C.; Steinberg, M. H. (Methods of Information in Medicine, 1997)
Health service restructuring in South Africa provides an opportunity to introduce appropriate Health Information System (HIS) technology. This is particularly relevant given the emerging HIV epidemic and the need to capture, translate and disseminate new experiences in HIV/AIDS care, support and clinical research. In 1994, a number of clinicians and health-care providers working in South Africa had begun to establish basic computerized databases to assist in research on HIV, but no standardized nomenclature or framework for collaboration was created. This paper describes a clinical and research database that could be used as an example for a standardized system by clinicians working in South Africa. The authors, with assistance from the National AIDS Research Programme of the Medical Research Council, created a prototype relational database using Microsoft Access™. To test the prototype, 1057 HIV-positive patients from the Infectious Disease Clinic at Johannesburg General Hospital were entered.
Keywords: Databases; Immunodeficiency Syndrome